2016
DOI: 10.1016/j.schres.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

A combined diffusion tensor imaging and magnetic resonance spectroscopy study of patients with schizophrenia

Abstract: Diffusion tensor imaging (DTI) studies in schizophrenia consistently show global reductions in fractional anisotropy (FA), a putative marker of white matter integrity. The cingulum bundle, which facilitates communication between the anterior cingulate cortex (ACC) and hippocampus, is frequently implicated in schizophrenia. Magnetic resonance spectroscopy (MRS) studies report metabolic abnormalities in the ACC and hippocampus of patients. Combining DTI and MRS offers exploration of the relationship between cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 92 publications
(149 reference statements)
4
22
0
Order By: Relevance
“…The absence of differences in AXD between patients and controls is consistent with previous whole brain voxel-wise studies (Kikinis et al, 2015;Lee et al, 2013;Reid et al, 2016;Scheel et al, 2013;Seal et al, 2008;Zeng et al, 2016), denoting preservation of axonal cells in the white matter (Song et al, 2003). This indicates that the decrease in FA in the patients, as reported previously (Domen et al, 2013), may not be related to a reduction in the number of axons.…”
Section: Non-fa Diffusivity Measuressupporting
confidence: 90%
See 1 more Smart Citation
“…The absence of differences in AXD between patients and controls is consistent with previous whole brain voxel-wise studies (Kikinis et al, 2015;Lee et al, 2013;Reid et al, 2016;Scheel et al, 2013;Seal et al, 2008;Zeng et al, 2016), denoting preservation of axonal cells in the white matter (Song et al, 2003). This indicates that the decrease in FA in the patients, as reported previously (Domen et al, 2013), may not be related to a reduction in the number of axons.…”
Section: Non-fa Diffusivity Measuressupporting
confidence: 90%
“…In the present study, clusters of significantly increased RD were dispersed over the brain and also represented in the corpus callosum of patients with psychotic disorder. Previous whole brain voxel-wise studies (K. Clark et al, 2012;Koch et al, 2011;Lu et al, 2011;Reid et al, 2016;Whitford et al, 2010) and region of interest based studies (McCarthy-Jones et al, 2015;Ohtani et al, 2014;Seitz et al, 2016) in psychotic disorder have found similar increases in RD, although some region of interest studies reported reduced RD in specific areas (Carletti et al, 2012;Kikinis et al, 2015;Koch et al, 2011). In addition, increased RD has been found in individuals at ultra high-risk for psychotic disorder (Carletti et al, 2012), suggesting that alterations may already be present in the prodromal stages.…”
Section: Non-fa Diffusivity Measuresmentioning
confidence: 99%
“…WM IC3 brainstem abnormalities could be indicative of the role the dopaminergic neurons in the brainstem play in thalamocorticostriatal circuit dysfunction implicated in schizophrenia (Ellison‐Wright et al, ). Furthermore, internal capsule abnormalities demonstrated in WM IC3 are supported by the literature (Di, Chan, & Gong, ; Horga et al, ; Lyu et al, ; Reid, White, Kraguljac, & Lahti, ). In fact, Horga and colleagues proposed that alterations in internal capsule could be a result of ventricular expansion consistently demonstrated in schizophrenia (Horga et al, ).…”
Section: Discussionsupporting
confidence: 72%
“…Basser and Pierpaoli 2011). Previous research on patients with psychotic disorder suggests that AXD is unaffected (Kikinis et al 2015;Reid et al 2016;Scheel et al 2013), whereas RAD and MD may be increased with respect to controls (Ardekani et al 2011;Clark et al 2011;Zeng et al 2016). In addition, higher levels of positive psychotic symptoms have been associated with a decrease in FA (Lener et al 2015;A.…”
Section: Introductionmentioning
confidence: 98%